BEDOUIN WOMEN STATUS UNDER THE PATRIARCHAL SYSTEM IN MIRAL AL TAHAWI’S THE TENT - Zainab Abd Ali Hammood; Lajiman Bin Janoory (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This research investigates the status of female characters under the oppressive patriarchal system of Bedouin in the novels of Miral Al Tahawi through the lens of radical feminist theory. Miral Al-Tahawi explains in her novel "The Tent" how women are marginalized and exploited in the context of parental restrictions imposed on them in Bedouin society, which is governed by harsh customs and values. The rationale comes from an understanding of the influence of this patriarchal authority over Bedouin women that reveals the status of women as oppressed and subject to the conditions that control women's identity and limit their freedom. This research will critically analyze the status of women in a gender-focused society. The current study found that Miral al-Tahawi embodied the suffering of Bedouin women through the suffering of the female characters in her novel. She reveals the extent of the suffering and patriarchal oppression that Bedouin women are subjected to in silence.